Pengaruh Likuiditas, Leverage, Komite Audit dan Perputaran Persediaan Terhadap Profitabilitas: Studi Empiris pada Perusahaan Sektor Consumer Cyclicals yang Terdaftar pada Bursa Efek Indonesia Periode 2019–2023 - Khairunisa Suci Putriani (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Companies with good performance are able to achieve the goals the company wants to achieve, namely maximizing profitability or company value. This goal can be achieved by increasing profitability within a company. The aim of this research is to determine the influence of liquidity, leverage, audit committee and inventory turnover on profitability in Consumer Cylicals sub-sector companies listed on the Indonesia Stock Exchange for the 2019-2023 period with a sample of 62 companies obtained through the purposive sampling method. The results of research using multiple linear regression analysis found that: (1) Liquidity, Audit Committee and inventory turnover have a positive and significant effect on profitability. (2) Leverage have a negative and significant effect on profitability.